Structure and content of the twitter colombian political sphere during the legislative elections of 2014 (2019)
The aim of the current article is to identify and analyze the structure and content of the twitter Colombian political sphere during the legislative elections of 2014, with the aim of knowing the characteristics and differences of this territory of virtual exchange with the traditional public space, and therefore be able to identify a single political public space for the South American country. This research project seeks to recognize how Twitter becomes a tool for the exchange of ideas and political arguments, therefore political messages posted on the microblogging tool are analyzed in order to compare what is happening in digital social networks and traditional media such as television and the national news, while the structure, actors and the content that is produced, exchanged and received through a digital public space are analyzed